GATA-1 interacts with the myeloid PU.1 transcription factor and represses PU.1-dependent transcription. - Nerlov, C; Querfurth, E; Kulessa, H; Graf, T (2000)
The GATA-1 transcription factor is capable of suppressing the myeloid gene expression program when ectopically expressed in myeloid cells. We examined the ability of GATA-1 to repress the expression and function of the PU.1 transcription factor, a central regulator of myeloid differentiation. We found that GATA-1 is capable of suppressing the myeloid phenotype without interfering with PU.1 gene expression, but instead was capable of inhibiting the activity of the PU.1 protein in a dose-dependent manner. This inhibition was independent of the ability of GATA-1 to bind DNA, suggesting that it is mediated by protein-protein interaction. We examined the ability of PU.1 to interact with GATA-1 and found a direct interaction between the PU.1 ETS domain and the C-terminal finger region of GATA-1. Replacing the PU.1 ETS domain with the GAL4 DNA-binding domain removed the ability of GATA-1 to inhibit PU.1 activity, indicating that the PU.1 DNA-binding domain, rather than the transactivation domain, is the target for GATA-1-mediated repression. We therefore propose that GATA-1 represses myeloid gene expression, at least in part, through its ability to directly interact with the PU.1 ETS domain and thereby interfere with PU.1 function. (Blood. 2000;95:2543-2551)